A New Pipe Routing Approach for Aero-Engines by Octree Modeling and Modified Max-Min Ant System Optimization Algorithm. (19th September 2016) - Qu, Y.-F.; Jiang, D.; Zhang, X.-L.
Abstract : Aero-engines usually contain a lot of pipes and cables which have an important influence on product performance and reliability. In this paper, a new pipe routing approach for aero-engines is proposed. First, an adaptive octree modeling method is presented according to the characteristics of the layout space. After considering three types of engineering constraints, the total length of pipelines, the total number of bends and the natural frequency of pipelines are modeled as the optimal objective. Then, a Modified Max-Min Ant System optimization algorithm (MMMAS), which uses layered node selection and dynamic update mechanism, is proposed for pipe routing. For branch pipelines, ant colony searches in groups and parallel to improve the solution quality and speed up the convergence greatly. Finally, numerical comparisons with other current approaches in literatures demonstrate the efficiency and effectiveness of the proposed approach. And a case study of pipe routing for aero-engines is conducted to validate this approach.